[Translated article] Efficacy of new active viscosupplements on the behaviour of an experimental model of osteoarthritis - R.E. Pérez Expósito; M.A. Ortega Núñez; M.J. Buján Varela; R.M. Vega Rodríguez; A.I. Ortíz Chércoles; B.J. De La Torre Escuredo (Revista Española de Cirugía Ortopédica y Traumatología)
Objective: To evaluate with an animal model of osteoarthritis (New Zealand rabbits) the effectiveness of treatment with active viscosupplements (hyaluronic acid loaded with nanoparticles (NPs) that encapsulate anti-inflammatory compounds or drugs. Material and methods: Experimental study composed of 5 groups of rabbits in which section of the anterior cruciate ligament and resection of the internal meniscus were performed to trigger degenerative changes and use it as a model of osteoarthritis. The groups were divided into osteoarthrosis without treatment (I), treatment with commercial hyaluronic acid (HA) (II), treatment with HA with empty nanoparticles (III), treatment with HA with nanoparticles encapsulating dexamethasone (IV) and treatment with HA with nanoparticles that encapsulate curcumin (V). In groups II–V, the infiltration of the corresponding compound was carried out spaced one week apart.Macroscopic histological analysis was performed using a scale based on the Outerbridge classification for osteoarthritis. Results: We observed that this osteoarthritis model is reproducible and degenerative changes similar to those found in humans are observed.The groups that were infiltrated with hyaluronic acid with curcumin-loaded nanoparticles (V), followed by the dexamethasone group (IV) presented macroscopically less fibrillation, exposure of subchondral bone and sclerosis (better score on the scale) than the control groups (I) (osteoarthritis without treatment), group (II) treated with commercial hyaluronic acid and hyaluronic acid with nanoparticles without drug (III). Conclusions: The use of active viscosupplements could have an additional effect to conventional hyaluronic acid treatment due to its antioxidant and anti-inflammatory effect. The most promising group was hyaluronic acid with nanoparticles that encapsulate curcumin and the second group was the one that encapsulates dexamethasone. Resumen: Objetivo: Evaluar con un modelo animal de osteoartrosis (conejos de raza Nueva Zelanda) la eficacia del tratamiento con viscosuplementos activos (ácido hialurónico [AH]) cargado con nanopartículas (NP) que encapsulan compuestos o fármacos antiinflamatorios. Material y métodos: Estudio experimental compuesto de cinco grupos de conejos a los que se realizó la sección del ligamento cruzado anterior (LCA) y resección del menisco interno para desencadenar cambios degenerativos y usarlo como modelo de osteoartrosis. Los grupos se dividieron en osteoartrosis sin tratamiento (I), tratamiento con AH comercial (II), tratamiento con AH con NP vacías (III), tratamiento con AH con NP que encapsulan dexametasona (IV) y tratamiento con AH con NP que encapsulan cúrcuma (V). En los grupos II a V se realizó la infiltración del compuesto correspondiente espaciándolas una semana.Se realizó un análisis histológico macroscópico mediante una escala basada en la clasificación de Outerbridge para la artrosis. Resultados: Observamos que dicho modelo de osteoartrosis es reproducible y se aprecian cambios degenerativos similares a los que se encuentran en el ser humano.Los grupos a los que se infiltró AH con NP cargadas con curcumina (V), seguido del grupo de dexametasona (IV) presentaron macroscópicamente menos fibrilación, exposición de hueso subcondral y esclerosis (mejor puntuación en la escala) que los grupos de control (I) (osteoartrosis sin tratamiento), el grupo (II) tratado con AH comercial y el de AH con NP sin fármaco (III). Conclusiones: El uso de viscosuplementos activos podría tener un efecto adicional al tratamiento convencional de AH por su efecto antioxidante y antiinflamatorio, siendo el grupo más prometedor el de las NP que encapsulan curcumina y en segundo lugar el de dexametasona.